Knowledge and Perceptions Role Towards Modern Male Contraceptives Use in Indonesia - Titis Risti Yulianti; Kemal Nazarudin Siregar; Milla Herdayati; Indra Supradewi (Jurnal Kesehatan Masyarakat, 2023)
The use of men's modern contraceptives is much lower than among women in Indonesia and there are quite large differences when compared to several countries in Asia because the use of men's modern contraceptives from 2002-2012 in Indonesia was always low due to a lack of knowledge and negative perception about Family Planning. This study aimed to determine the role of knowledge and perceptions of family planning for use of men's modern contraceptives in Indonesia. This research method used a cross-sectional design on a secondary basis based on the 2017 IDHS. The result of this study is that there is a relationship between knowledge and perception of family planning in the use of men's modern contraceptives after being controlled by education level, area of residence, and fertility preferences. This study concludes that married men who use modern contraceptives are those who have good knowledge and positive perceptions about family planning, which are found in married men who have a high level of education, live in urban areas, and do not want to have children anymore. This study recommends a special male family planning program based on gender justice by prioritizing special substances regarding family planning knowledge and perceptions.